2007
DOI: 10.1024/2007.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Chronic khat use and psychotic disorders: A review of the literature and future prospects

Abstract: Aims: In recent decades, the traditional habit of chewing the khat leaves, which contain the amphetamine-like cathinone, has undergone profound changes in African and Arab countries, from a socially regulated use pattern to uncontrolled consumption. This is of special public mental-health concern. In this article, a review of the scientific literature on the relationship between khat use and psychosis is provided. Results: Several case studies, but only a few group and community-based studies, have addressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 88 publications
(118 reference statements)
6
72
1
1
Order By: Relevance
“…Few reports from Yemen and elsewhere have indicated that chronic khat consumption may be a leading cause of cancer, cellular toxicity and other metabolic disorders [10][11][12][13]. An extensive review by Al-Motarreb et al [8] and Odenwald [9] about khat chewing and cellular toxicity revealed that some of the literature reports contradicted each other and that the rest were inconclusive as a result of limited data quality and depth. The current understanding of many khat-related topics is still poor and thus further research is urgently needed [14].…”
Section: (-)-Cathinone [(S)-α-aminopropiophenone] (+)-Cathine [(1s) mentioning
confidence: 97%
See 1 more Smart Citation
“…Few reports from Yemen and elsewhere have indicated that chronic khat consumption may be a leading cause of cancer, cellular toxicity and other metabolic disorders [10][11][12][13]. An extensive review by Al-Motarreb et al [8] and Odenwald [9] about khat chewing and cellular toxicity revealed that some of the literature reports contradicted each other and that the rest were inconclusive as a result of limited data quality and depth. The current understanding of many khat-related topics is still poor and thus further research is urgently needed [14].…”
Section: (-)-Cathinone [(S)-α-aminopropiophenone] (+)-Cathine [(1s) mentioning
confidence: 97%
“…The short term chewing effects have been well discussed [2,8,9] however, not so much information is available regarding the long-term health impact of chewing khat. Few reports from Yemen and elsewhere have indicated that chronic khat consumption may be a leading cause of cancer, cellular toxicity and other metabolic disorders [10][11][12][13].…”
Section: (-)-Cathinone [(S)-α-aminopropiophenone] (+)-Cathine [(1s) mentioning
confidence: 99%
“…In the mental health domain, studies show that khat is functionally used by people with Posttraumatic Stress Disorder (PTSD) and other mental disorders to achieve temporary relief from their symptoms (Bhui et al, 2003;Odenwald et al, 2009); and that excessive khat use is associated with the development of psychotic symptoms which may be brief or persistent (Odenwald et al, 2009;Odenwald, 2007;. Odenwald et al (2009) recently illustrated the causal mechanism for khat-induced paranoid symptoms among combatants.…”
Section: What Is Behind the Growing International Khat Concerns?mentioning
confidence: 99%
“…In the present commentary, we call for a balanced and informed response to the growing concerns about this neglected psychoactive drug that possibly is a contributory factor in widespread social and psychological suffering in several countries where there are virtually no specialist mental health services and systems (Odenwald, 2007;Bhui and Warfa, 2007) and that more and more develops into the economic backbone for millions of farmers and traders. Three decades of futile discussions (International Narcotic Control Board, 2006) have not led to sustainable measures being taken while in a downward spiral, suffering related to abuse and economic dependency on the khat sector has become ever more severe and widespread.…”
Section: Khat: the Bitter Sweet Leavesmentioning
confidence: 99%
“…Si chez beaucoup d'usagers les troubles psychiques restent mineurs, de nombreuses observations suggèrent un lien entre des troubles mentaux plus sévères et la consommation de khat [29,35,36]. Sont particulièrement discutés des épisodes psychotiques, accès maniaques, troubles schizophréniques et paranoïaques [12,37].…”
Section: Effets Sur Le Système Nerveux Centralunclassified